Mendefinisikan Kembali Sdm: Memupuk Budaya Perbaikan Dan Inovasi Yang Berkelanjutan - Rika Solihah; Sonny Sanjaya; Dady Indra Permana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study investigates the impact of Human Resource Practices on the Culture of Continuous Improvement and Innovation, with Employee Engagement and Leadership Support serving as intervening variables. Employing a quantitative research design, the study utilized a sample of 93 employees from PT Lucas Djaja, determined through random sampling and Slovin’s formula. Data were analyzed using Smart PLS to explore the relationships between the variables. The results reveal that Human Resource Practices significantly influence both Employee Engagement and Leadership Support. Moreover, both Employee Engagement and Leadership Support positively mediate the relationship between Human Resource Practices and the Culture of Continuous Improvement and Innovation. These findings emphasize the critical role of strategic Human Resource Practices in fostering an organizational culture that supports ongoing improvement and innovation. The study highlights the need for organizations to integrate effective Human Resource strategies, engage employees, and support leadership to enhance continuous improvement and innovation.